Cochlear volume as a predictive factor for residual-hearing preservation after conventional cochlear implantation. (3rd April 2018) - Takahashi, Masahiro; Arai, Yasuhiro; Sakuma, Naoko; Yabuki, Kenichiro; Sano, Daisuke; Nishimura, Goshi; Oridate, Nobuhiko; Usami, Shin-ichi
Abstract: Objective: The preservation of residual hearing after conventional cochlear implantation (CI) is frequently observed when atraumatic soft surgery is adopted. The purpose of this study was to elucidate the predictive factors for residual hearing preservation after atraumatic CI. Patients: This study included 46 patients who underwent CI based on an atraumatic technique using a standard-length flexible electrode implant through a round window approach. Main outcome measure: Cochlear volume was measured using magnetic resonance imaging (MRI). Cochlear duct length (CDL) was taken as the length of the scala media measured using computed tomography (CT). The association between residual hearing preservation and cochlear volume/CDL was then examined. Result: Cochlear volume and CDL were significantly larger in patients with complete hearing preservation than in those with hearing loss. Multivariate logistic regression analysis revealed that cochlear volume was a significant predictive factor for residual hearing preservation. Conclusion: Residual hearing preservation after conventional CI was observed in patients with a larger cochlear volume and longer CDL. Cochlear volume could be a predictive factor for residual hearing preservation after conventional CI.